Beyond Collapse: The Message of COVID–19 to the Sri Lankan Tourism Industry - Sivanandamoorthy Sivesan (Journal of Tourismology)
The coronavirus (COVID – 19) is a grave and rapidly growing health concern, which not only affects Chinese economic growth but which also has a serious impact on the global economy. The tourism industry has made, and continues to make, a valuable contribution to Sri Lankan economic and socio cultural development. This research study describes how far Sri Lanka tourism industry has collapsed due to the COVID – 19? how can Sri Lanka possibly reshape of as a leading tourist destination in the world market? This study suggests two phases of different strategies to reshape the Sri Lankan tourism market. Phase 01 deals with short terms remedies to the current problem which has arisen due to the health crisis. SLTDA should begin to work with the Ministry of Health and Indigenous Medical Services in the following ways: Issuing certificates to hotels to ensure the health and safety management of the hotels’ staff, tourists and host community as well as security and hygiene arrangements at airports. Preparing detailed guidelines to establish quarantine hotels with employee safety and ensuring health safety of tourist guides and tourism related business. Phase 02 deals with with long–term strategies to rebuild the tourism industry in Sri Lanka.